Factors influencing E-pharmacy adoption in India: A study of user experiences through interpretative phenomenological analysis - Kushal Pal Singh; Pawan Kumar (Exploratory Research in Clinical and Social Pharmacy)
The rapid growth of e-commerce has led to the emergence of e-pharmacies, which enable consumers to purchase prescription medications online. This study aims to explore the factors influencing the adoption of e-pharmacies in India through an interpretative phenomenological analysis (IPA) approach. Twelve in-depth interviews were conducted with individuals who had experience ordering prescription medicines through e-pharmacies. The findings revealed that constructs from the UTAUT2 model, including performance expectancy, effort expectancy, social influence, facilitating conditions, price value, and habit, played a significant role in the adoption of e-pharmacies. Construct hedonic motivation, from UTAUT2, was found to be weakly significant in explaining the adoption of e-pharmacy. Additionally, health literacy was identified as a key factor, with e-pharmacy users demonstrating higher levels of health literacy. However, perceived risks, such as performance, financial, privacy, and psychological risks, were found to negatively influence the adoption of e-pharmacies. The study proposes, based on findings, a research model to understand consumer behavior in the adoption of e-pharmacies. The findings suggest that the presence of favorable conditions, such as convenience, accessibility, user-friendly interfaces, social influence, internet accessibility, integrated healthcare services, diverse payment methods, and price advantages, have contributed to the widespread acceptance and adoption of e-pharmacy services in India. The study highlights the need for future research to employ quantitative or mixed methods approaches to address the limitations of the current exploratory study and to investigate the multifaceted determinants of e-pharmacy adoption in different geographical contexts.